Chemical constituents of the Egyptian Plant Anabasis articulata (Forssk) Moq and its antidiabetic effects on rats with streptozotocin-induced diabetic hepatopathy - Nadia S Metwally, Azza M Mohamed, Fatma S ELSharabasy (Journal of Applied Pharmaceutical Science)
This study investigated the possible antidiabetic role and therapeutic crucial action of the saponin fractions of the ethanolic extract of areal parts of the medicinal plant Anabasis articulata compared to currently available antidiabetic drug gliclazide (diamicron) against diabetic complications induced tissue injury in rats. Fractionation of hydro alcoholic extract from the aerial parts of Anabasis articulata (Chenopodiaceae) led to the isolation of Four known saponins: 3-O-glucopyranosyl of(stigmasterol, ß-sitosterol, sitostanol), 3-O-[ß-D- the glucopyranosyl] oleanolic acid , 3-O-[ß-D-glucopyranosyl -28-O-ß-D - xylopyranosyl] oleanolic acid, in addition to proceric acid. The isolated compounds were identified by means of chemical methods and spectrometric analysis as Rf values, UV Mass, 1H NMR and 13CNMR spectroscopy. Animals were divided into 4 groups. Group1, control rats (not received any medication). Group 2, rats injected intraperitoneally with single dose of streptozotocin (STZ)(40 mg/kg body weight). Group 3, rats orally administered with ethanolic extract of A. articulata (400 mg/ kg B.W.) after STZ injection. Group 4, rats orally administered with gliclazide (10 mg/kg B.W.) after STZ injection. Oral administration of the plant modulated the diabetic increase in blood glucose and cortisol levels revealing the antihyperglycemic effect of this medicinal plant. It effectively increases the blood hormone insulin concentration and α- fetoprotein. It is also significantly decrease blood tumor necrosis factor α (TNF-α). The current plant also effectively decreased blood fructosamine to their normal levels as well as the consequence diabetic decrease in the hemoglobin (Hb) and albumin levels. Furthermore, ingestion of the plant effectively modulated hepatic oxidative tissue damage. Supplementation of diabetic animals with gliclazide improved diabetic induced alteration in most of the above studied markers. These results suggest that Anabasis articulata has multi-beneficial actions in controlling diabetes and consequence complications induced in pancreas and liver and may candidate as natural antidiabetic drug.
Keywords: Diabetes, Streptozotocin, Anabasis articulata, Saponins, glycation,Gliclazide.